1999
DOI: 10.1111/j.1745-4514.1999.tb00035.x
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenolic Substrates of Cationic and Neutral/Anionic Peroxidases From Barley and Malt Using a Chronometric Method for the Determination of Pod Activity

Abstract: 4‐methylcatechol, phenolic acids from the benzoic and cinnamic series, flavan 3‐ols and L‐tyrosine were tested to determine the catalytic behavior of barley peroxidases (POD) at the expense of hydrogen peroxide. A chronometric assay using L‐ascorbic acid was described for determining the peroxidatic activity of basic and neutral/anionic enzymatic fractions. The effects of hydrogen donors H2O2, and Ca++ ion concentrations and pH were studied to set maximal conditions for POD measurement. The sensitivity to endo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 28 publications
1
3
0
Order By: Relevance
“…As already found for other PODs ( , ), in the presence of AA, a lag period was apparent before any change in absorbance at 310 nm ( Figure 8 a ) whereas the decrease of absorbance at 266 nm was immediate. In our conditions (H 2 O 2 = 500 μM), the duration of the lag period was almost proportional to the AA concentation until 200 μM and then increased rapidly to become infinite as the AA concentration was increased to 500 μM.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…As already found for other PODs ( , ), in the presence of AA, a lag period was apparent before any change in absorbance at 310 nm ( Figure 8 a ) whereas the decrease of absorbance at 266 nm was immediate. In our conditions (H 2 O 2 = 500 μM), the duration of the lag period was almost proportional to the AA concentation until 200 μM and then increased rapidly to become infinite as the AA concentration was increased to 500 μM.…”
Section: Resultssupporting
confidence: 83%
“…Recently, Labat et al ( , ) have shown that the oxidation of FA either free or esterified is accelerated by laccase and manganese POD during mixing of wheat flour dough or of a mix of wheat gluten and pentosans. Although several authors have recently studied the effect of plant PODs on FA and on the structure of the diferulate ( ), to our knowledge, the effect of a POD extract from wheat flour has never been studied with this substrate. Therefore, the aim of this paper is to study the oxidation of FA and 5-O-( trans -feruloyl)- l -arabinose (EFA) by the H 2 O 2 /wheat POD system.…”
Section: Introductionmentioning
confidence: 99%
“…Peroxidases (POD) from barley are heat-stable enzymes responsible for phenolic substrate oxidative polymerization, which caused the increased color and turbidity of wort. 33,34 They have been found to be in more abundance in Dan'er malt compared with Metcalfe malt. 11 Furthermore, the activity of POD was higher in Dan'er malt than in Metcalfe (Supporting Information supplementary Figure 5).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…However, there was no significant change of polyphenol concentrations in the wort using Metcalfe malt by adding a similar amount of BSZ7 (Supporting Information supplementary Figure 4), indicating there is an enzyme promoting the cross-link, and this enzyme was in a different redundancy or exhibited distinct activity between these two malts. Peroxidases (POD) from barley are heat-stable enzymes responsible for phenolic substrate oxidative polymerization, which caused the increased color and turbidity of wort. , They have been found to be in more abundance in Dan’er malt compared with Metcalfe malt . Furthermore, the activity of POD was higher in Dan’er malt than in Metcalfe (Supporting Information supplementary Figure 5).…”
Section: Resultsmentioning
confidence: 99%